Complications in ascending aortic aneurysm surgery: a single centre experience of 81 patients - Emced Khalil (Medicinski glasnik, 2019)
Aim: To investigate major in-hospital complications of ascending aorta reconstruction and to identify factors associated with these complications. Methods: All consecutive patients admitted to our clinic for aortic aneurysm repair from June 2005 to June 2009 were enrolled in this retrospective study. Demographic data, details of the surgical procedures and major in-hospital complications were assessed and recorded from the institutional electronic database. Patients were divided into two groups according to the development of major in-hospital complications. Results: The New York Heart Association (NYHA) Class of patients with major in-hospital complications was higher than those without complications. In addition, the number of patients with coronary artery disease (CAD), diabetes, chronic renal disease (CRD), chronic obstructive pulmonary disease (COPD), and previous cardiac surgery was significantly higher in those with major in-hospital complications. Moreover, the requirement for inotropic agents and intra-aortic balloon pump was higher in these patients. Cross-clamp time was significantly higher in patients with major in-hospital complications (107±34 vs. 79±26 (p<0.001). Presence of CRD (r=0.308; p=0.005) and CAD (r=0.244; p=0.028), previous cardiac surgery (r=0.266; p=0.022), cross-clamp time (r=0.349; p=0.001) and IABP requirement (r=0.308; p=0.005) were significantly correlated with the development of major in-hospital complications. Conclusion: Our results show that presence of underlying CRD and CAD, previous cardiac surgery, length of cross-clamp time and IABP requirement were significantly associated with the development of in-hospital complications in patients undergoing surgical reconstruction for ascending aortic aneurysm.
Keywords: ascending aortic aneurysm; complications; mortality; surgery